(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Information Technology (IT) is one of the most important industries in the state in which the two or more people are involved in communication. At this point, the company’s workforce grew and employees came up with unsolicited situations due to stress. The globalization of the economy has forced our IT staff to take more care of their individual capacities. This paper mainly analyses the impact of stress on employees work commitment in Indian IT companies.